Mudança no modelo de negócio, percepção de valor dos clientes e seus reflexos na apropriação de valor: um estudo no setor de cartões de crédito - D'Andrea, Daniel (2016)
The main objective of this work is to analyse the impact caused by business model changes, mainly regarding the value proposition, over the clients´ perceived value, and consequently, its effect upon the captured value for the company. In addition, it has the further following objectives: the understanding of business model changes, and their impacts on other business model elements. The study was conducted in the Brazilian credit card sector and was designed and developed using three different methodological techniques: i) interviews with companies and with market experts; ii) on-line surveys with clients of a credit card operator (for measuring the clients´s perceived value before and after the change); and iii) a secondary data analysis also conducted with credit card operator clients, comparing the usage patterns in two periods (before and after the change). The findings not only confirmed the two proposed research hypothesis (a business model change impacts the clients´perceived value and also the value captured by the company), but also gave a quantitative indication of the degree of impact. Apart from this, the interviews revealed relevant findings about the business model change process in the sector, as well as the main challenges faced by companies. These findings provide a significant contribution for the research field of business models and perceived value, and further reveal useful lessons and practical implications for all those involved in these areas.